A New Devonian Modiolopsidae (Mollusca: Bivalvia) from the Ponta Grossa Formation, Paraná Basin, Brazil - KOTZIAN, CARLA BENDER (Pesquisas em Geociências, 2003)
<!-- .p { text-align: justify; } --> This paper describes the bivalve Modiolopsis (?) clarkei n. sp, coming from the Curva I outcrop, Ponta Grossa Formation. The species name was given in honor to J. M. Clarke, who first studied it. This fossil also occurs in the Durazno Group, in Uruguay, reinforcing the correlation between the Devonian Paraná Basin invertebrate fauna with others of the Malvinocaffrik Realm, as suggested by previous authors. The classification of M. (?) clarkei in a typical Ordovician genus or lineage, that can reach the Silurian and Lower Devonian periods, supports an Emsian age to the Curva I outcrop, as have been accepted.